Monetary Policy Transmission Mechanisms in Pacific Island Countries - Dunn, Jonathan; Davies, Matt.; Wu, Yiqun; Yang, Yongzheng (Washington, D.C. : International Monetary Fund, 2011)
During the global financial crisis, central banks in Pacific island countries eased monetary policy to stimulate economic activity. Judging by the ensuing movements in commercial bank interest rates and private sector credit, monetary policy transmission appears to be weak. This is confirmed by an empirical examination of interest rate pass-through and credit growth. Weak credit demand and underdeveloped financial markets seem to have limited the effectiveness of monetary policy, but the inflexibility of exchange rates and rising real interest rates have also served to frustrate the central banks' efforts despite a supporting fiscal policy. While highlighting the importance of developing domestic financial markets in the long run, this experience also points to the need to coordinate macroeconomic policies and to use all macroeconomic tools available in conducting countercyclical policies, including exchange rate flexibility.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet